2007
DOI: 10.4161/psb.2.1.3596
|View full text |Cite
|
Sign up to set email alerts
|

Do Plant Cells Secrete Exosomes Derived from Multivesicular Bodies?

Abstract: Multivesicular bodies (MVBs) are spherical endosomal organelles containing small vesicles formed by inward budding of the limiting membrane into the endosomal lumen. In mammalian red cells and cells of immune system, MVBs fuse with the plasma membrane in an exocytic manner, leading to release their contents including internal vesicles into the extracellular space. These released vesicles are termed exosomes. Transmission electron microscopy studies have shown that paramural vesicles situated between the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 30 publications
2
85
0
Order By: Relevance
“…14 This evidence obtained in our laboratory joins additional observations of An et al, 15,16 who reported the release of exosome-like vesicles in barley leaves attacked by a pathogenic fungus. Recently, Wang et al 17 have reported the presence of EXPO, exosome-like structures released by Arabidopsis and tobacco cells, probably associated to unconventional secretion.…”
Section: Apoplastic Vesicles and Proteins Without Predicted Signal Pesupporting
confidence: 77%
“…14 This evidence obtained in our laboratory joins additional observations of An et al, 15,16 who reported the release of exosome-like vesicles in barley leaves attacked by a pathogenic fungus. Recently, Wang et al 17 have reported the presence of EXPO, exosome-like structures released by Arabidopsis and tobacco cells, probably associated to unconventional secretion.…”
Section: Apoplastic Vesicles and Proteins Without Predicted Signal Pesupporting
confidence: 77%
“…However, the membrane invaginations in the leaf AZ of Phaseolus vulgaris (Webster, 1973) have gained renewed attention of late, with regard to their association with multivesicular bodies (MVBs) and PBs. MVBs are redirected to the plasma membrane, where they release their contents, including internal vesicles captured in PBs, into the extracellular space by membrane fusion (reviewed in An et al, 2007). Similar structures have been recently described during Arabidopsis floral organ abscission (Liljegren et al, 2009).…”
Section: Abscission Is Impeded In Transgenic Plants Overexpressing Anmentioning
confidence: 97%
“…The secretion of EVs is highly conserved and has been demonstrated in bacteria (Kulkarni and Jagannadham 2014, Kaparakis-Liaskos and Ferrero 2015), protozoa (Mantel and Marti 2014), insects (Beckett, Monier et al 2013), plants (An, van Bel et al 2007, Mu, Zhuang et al 2014, Samuel, Bleackley et al 2015) and mammals (Colombo, Raposo et al 2014). There are several categories of EVs: apoptosomes that are released from cells undergoing apoptosis, microvesicles that are released by evagination of the plasma membrane, and exosomes which are generated by the fusion of multivesicular bodies (MVB) with the plasma membrane and the release of intraluminal vesicles (ILV) into the extracellular fluid (Figure 1) (Colombo, Raposo et al 2014, Yanez-Mo, Siljander et al 2015).…”
Section: Introductionmentioning
confidence: 99%